Poetry and Motion: Rhythm, Rhyme and Embodiment as Oral Literacy Pedagogy for Young Additional Language Learners - Natasha Elizabeth Beaumont (MDPI AG, 2022)
Literacy pedagogy that integrates oracy, poetry and embodiment can foster children's language development in multiple ways: (1) oracy is foundational to children's emergent literacy as writing extends from oral language, (2) poetry uses rhythm and rhyme to support letter-recognition and the learning of phonemes and morphemes, (3) embodiment and roleplay provide semiotic support and opportunities for expressive and receptive communication. This article shares findings from a phenomenological case study investigating how literacy pedagogy that integrated oracy, poetry and embodiment impacted three additional language students aged 6. A series of weekly literacy classes in a school in Sydney's multicultural western region were observed and recorded on video. This instrument was able to capture 'micro-moments' of learning between peers, depicting how physicalisation and the use of rhythm and rhyme effectively engaged students whose first language was not used in the classroom. Using a hermeneutic phenomenological approach to data analysis, case study findings revealed that embodied explorations of poetry immersed participants socially and imaginatively whilst pushing them beyond their additional language comfort zone. The pedagogy was also shown to increase comprehension and support the acquisition of new vocabulary.